2012
DOI: 10.1029/2012je004118
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER detection of electron‐induced X‐ray fluorescence from Mercury's surface

Abstract: [1] The X-Ray Spectrometer (XRS) on the MESSENGER spacecraft measures elemental abundances on the surface of Mercury by detecting fluorescent X-ray emissions induced on the planet's surface by the incident solar X-ray flux. The XRS began orbital observations on 23 March 2011 and has observed X-ray fluorescence (XRF) from the surface of the planet whenever a sunlit portion of Mercury has been within the XRS field of view. Solar flares are generally required to provide sufficient signal to detect elements that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…These observations suggest that the electrons could drift in longitude along closed field lines, as demonstrated in a few cases at higher energies by echoes [ Baker et al , ], and that there could be quasi‐trapped electrons in orbits close to Mercury's magnetic equator as a more or less standard feature. We refer to these particles as quasi‐trapped because most of the electrons at these energies (~ keV) cannot completely drift around the planet before either striking the surface or hitting the dayside magnetopause, and only a few make a complete orbit around the planet [ Schriver et al , ; Starr et al , ]. However, the fact that we detected these electrons on almost every orbit indicates that they represent a semipermanent feature.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…These observations suggest that the electrons could drift in longitude along closed field lines, as demonstrated in a few cases at higher energies by echoes [ Baker et al , ], and that there could be quasi‐trapped electrons in orbits close to Mercury's magnetic equator as a more or less standard feature. We refer to these particles as quasi‐trapped because most of the electrons at these energies (~ keV) cannot completely drift around the planet before either striking the surface or hitting the dayside magnetopause, and only a few make a complete orbit around the planet [ Schriver et al , ; Starr et al , ]. However, the fact that we detected these electrons on almost every orbit indicates that they represent a semipermanent feature.…”
Section: Discussion and Summarymentioning
confidence: 96%
“…Do these measurements provide additional evidence for particle loss at Mercury's surface associated with its asymmetric magnetic field, as suggested by Korth et al . [], and as shown with measurements of electron‐induced X‐ray fluorescence [ Starr et al ., ]?…”
Section: Summary and Future Workmentioning
confidence: 99%
“…Closer examination reveals that these events are short, with durations equal to or less than the instrument integration period (3 s). This group of events could be related to the low‐energy, low‐intensity X‐ray fluorescence events observed during MESSENGER's low‐latitude flybys [ Ho et al , 2011a] and seen near the planet from orbital XRS observations [ Starr et al , 2012]. Prompted by the low‐energy electron (1–10 keV) events seen during the flybys, Schriver et al [2011] reported kinetic simulation results that suggested a quasi‐trapped population of low‐energy (1–10 keV) ions and electrons near Mercury's equatorial region.…”
Section: Statistical Analysis Of Energetic Electron Bursts At Mercurymentioning
confidence: 99%